2015
DOI: 10.5455/ijmsph.2015.25122013194
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoglyphic analysis of fingertip and palmer print patterns of obese children

Abstract: psychiatry, and anthropology. Different diseases have different finger prints associated with them. It is clear now that in near future, owing the recent advancement in the field of dermatoglyphics, it is possible to predict that an individual is having or will have that disease. Obesity is a multifactorial condition (polygenic and environmental). Factors determining obesity in utero may influence dermatoglyphic patterns. Dermatoglyphic patterns can be used as a marker to detect obesity. Hence, this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 5 publications
2
9
2
Order By: Relevance
“…In the city of São Paulo, Brazil, a survey ( Pasetti et al ., 2012 ) with 30 obese Brazilian women with a mean age of 46.1 ± 07.87 years, all with a BMI equal to or greater than 30, observed that participants presented a high frequency of the arch pattern, low frequencies of the ulnar loop pattern and a high frequency of the whorl pattern. These results corroborate the findings of several other authors ( Bhardwaj et al ., 2015 ; Oladipo et al ., 2010 ) who also presented a predominance of the arch pattern in the obese group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the city of São Paulo, Brazil, a survey ( Pasetti et al ., 2012 ) with 30 obese Brazilian women with a mean age of 46.1 ± 07.87 years, all with a BMI equal to or greater than 30, observed that participants presented a high frequency of the arch pattern, low frequencies of the ulnar loop pattern and a high frequency of the whorl pattern. These results corroborate the findings of several other authors ( Bhardwaj et al ., 2015 ; Oladipo et al ., 2010 ) who also presented a predominance of the arch pattern in the obese group.…”
Section: Discussionsupporting
confidence: 93%
“…In one sample of 370 obese children, in a study to identify dermatoglyphic patterns in obese individuals and to discover the association between standard dermatoglyphics and obesity, a high frequency of the arch pattern was observed in the right thumb ( Bhardwaj et al ., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A result which was in accordance with an Indian study 2009 [7], a Sri Lanka study 2013 [21] with higher records on the ring finger, an Indian people 2015 [28,40] with also higher records on the ring finger. A 3 rd Indian study in 2015 [41] recoded high frequencies for the whorls on the index and thumb, with nearly equal ratios on the middle and ring fingers. Also the present results for whorls were consistent with a Thailand study 2013 [14], an Indian study 2006 [28] for the ring, thumb and index fingers.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal programming of diseases and conditions can originate during this period [ 18 ]. In this connection, studies have been carried out in order to identify dermatoglyphic traits that can be associated with different types of diseases and conditions [ 19 , 20 ], including obesity [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%